Analysis of Accident Characteristics and Accident-Prone Areas in Sleman Regency, Yogyakarta (Case Study: Kaliurang Road Section Km 3.5 – Km 10) - Hay, Maria Lovernia; Ansusanto, J Dwijoko (ASTONJADRO, 2023)
This study aims to identify accident-prone locations on the Kaliurang road km 3.5 – km 10 Sleman Regency, D.I.Yogyakarta Province to find steps to reduce accidents in these accident-prone areas. The initial data is traffic accident data for 2020 – March 2022 which is then analyzed to determine the characteristics of traffic accidents on the Kaliurang km 3.5 – km 10 road segment classified by type of collision, type of vehicle, and material loss. Determination of the location of accident-prone areas based on ranking using the Equivalent Accident Number (EAN). A total material loss of Rp. 86,300,000.00 for the last two years and three months. The location of the accident-prone area is the Kaliurang kilometer 8 road with an EAN value of 203. The results of the analysis are interpreted that the better the handling related to complementary buildings and road facilities, the more likely it is to reduce the number of accidents in the accident-prone area.